Solid waste-based high-fluidity filling material and preparation method thereof

By using copolymerized silicone polycarboxylic acid water reducing agent in the red mud-based filling material, the problems of increasing viscosity and decreasing fluidity caused by alkali excitation in the prior art are solved, and the slurry fluidity and filling material strength are optimized.

CN119638357AActive Publication Date: 2025-03-18UNIV OF SCI & TECH BEIJING +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411834399.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing red mud-based filling materials increase viscosity and reduce fluidity during the gelling reaction due to alkali excitation, and are prone to blocking the pipe. At the same time, the water reducing agent interacts with solid waste gelling particles in a high alkali environment, resulting in less obvious water reduction effect, deterioration of the fluidity of the slurry, and the strength cannot be optimized.

Method used

The silicone polycarboxylic acid water reducing agent made of copolymerized carboxylic acid monomer, polyethylene glycol monoallyl ether and silane monomer enhances the electrostatic repulsion between solid waste gel particles through the balance of the hydrophilic regional structure, prevents the water reducing agent from being wrapped, and improves the fluidity of the slurry and the strength of the filling material.

Benefits of technology

The slurry flowability and filling material strength are optimized, with an initial flow degree of more than 350mm and a 30min flow degree retention value of more than 320mm, ensuring efficient flow and stable strength of the filling material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638357A_ABST
    Figure CN119638357A_ABST
Patent Text Reader

Abstract

The invention provides a solid-waste-based high-fluidity filling material and a preparation method thereof. The solid-waste-based high-fluidity filling material comprises 40-60 parts of Bayer process red mud, 40-60 parts of fly ash, 10-20 parts of desulfurized gypsum, 3-5 parts of a pumping agent and 30-60 parts of water, and the pumping agent is prepared by compounding an organosilicon polycarboxylic acid water reducer, polymaleic acid and water-soluble cellulose according to the mass ratio of (3-5): (3-5): 10; the organic silicon polycarboxylic acid water reducer is formed by copolymerizing unsaturated carboxylic acid monomers, polyethylene glycol monoallyl ether and unsaturated silane monomers in a mass ratio of (1.5-2): (2-4): (0.8-1) in the presence of a chain transfer agent. A hydrophobic area is formed by the silane monomer, the electrostatic repulsion effect between solid waste gel particles with the water reducing agent adsorbed on the surfaces is enhanced through structural balance of the hydrophobic area and the hydrophilic area, the situation that the water reducing agent is wrapped by the solid waste gel particles is prevented, and the fluidity of slurry and the strength of the filling material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of filling materials, and in particular relates to a solid waste-based filling material and a preparation method thereof. Background Art

[0002] my country has a vast land area, rich mineral resources and a large population, so it has always been a major country in energy mining and use. The tunnels and goafs left after resource mining and the rock cracks caused by mining are potential hidden dangers that affect the stability of the strata. When the overlying rock mass moves under the action of gravity and stress, it will cause strong surface movement, and in severe cases, surface subsidence and continuous mine tremors will occur. Filling and managing goafs can reduce the safety risks of mines, improve resource recovery rate and comprehensive utilization rate, reduce the demand for new resources and promote the sustainable development of mines.

[0003] According to different transportation technologies, the filling methods of goaf can be divided into hydraulic filling method, dry filling method and cement filling method. Since cement filling has the characteristics of low operating cost, good mechanical properties and mature technology, it has been widely used. Grouting cement filling material is a kind of backfill material with high fluidity, which can be filled by itself through its own weight or a little vibration to form a self-compacting structure. Its strength requirement is low. Therefore, industrial solid waste alkali-activated cementitious materials rich in Si, Al and Ca can be used as filling materials, such as red mud, coal gangue, fly ash, slag, etc. These materials have the advantages of low cost and environmental protection, and have significant social significance and economic benefits. For example, the red mud-based fluid expansion filling material disclosed in patent CN102101788B, a Bayer process red mud-based filling material and its preparation method disclosed in CN111393097B.

[0004] The above technology is a filling material with red mud and fly ash as the main cementing materials, which realizes the green utilization of solid waste and reduces the cost of filling materials. However, the pH of the red mud leaching solution can reach 12-14, and its alkali-induced gelling reaction will significantly increase the viscosity of the slurry, weaken its fluidity, and easily cause pipe blockage. In addition, red mud and fly ash themselves have large specific surface areas, and the slurry containing red mud and fly ash belongs to a high-alkaline environment. The interaction between the solid waste gelling particles and the anion-containing water reducer is stronger. The water reducer is easily wrapped in the solid waste gelling particles and is difficult to contact with water, resulting in an insignificant water reduction effect, deterioration of slurry fluidity, and failure to optimize strength.

[0005] Therefore, it is necessary to develop a solid waste-based filling material that can not only ensure the optimization of mechanical properties but also have excellent slurry fluidity. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a high-fluidity filling material for solid-base waste and a preparation method thereof. The filling material contains an organosilicon polycarboxylic acid water-reducing agent copolymerized by carboxylic acid monomer, polyethylene glycol monoallyl ether and silane monomer. The chain segments formed by the silane monomer increase the charge density of the hydrophilic region while increasing the hydrophobic region. Through the balance of the hydrophilic and hydrophobic regional structures, the electrostatic repulsion between the solid waste gelled particles with the water-reducing agent adsorbed on the surface is enhanced, the occurrence of the solid waste gelled particles wrapping the water-reducing agent is prevented, and the fluidity of the slurry and the strength of the filling material are improved. In addition, under the joint action of the hydrophilic group and the hydrophobic group, a thicker solvated water film will be formed on the surface of particles such as red mud, which will further reduce the viscosity between the particles and improve the fluidity of the slurry.

[0007] In order to achieve the above purpose, the following technical solutions are adopted:

[0008] A solid waste-based high-fluidity filling material comprises the following raw materials in parts by weight: 40-60 parts of Bayer red mud, 40-60 parts of fly ash, 10-20 parts of desulfurized gypsum, 3-5 parts of pumping agent, and 30-60 parts of water, wherein the pumping agent is a compound of an organosilicon polycarboxylic acid water-reducing agent, polymaleic acid, and water-soluble cellulose in a mass ratio of 3-5:3-5:10, and the organosilicon polycarboxylic acid water-reducing agent is copolymerized by an unsaturated carboxylic acid monomer, polyethylene glycol monoallyl ether, and an unsaturated silane monomer in a mass ratio of 1.5-2:2-4:0.8-1 in the presence of a chain transfer agent.

[0009] The unsaturated carboxylic acid monomer is selected from one or a combination of two or more of acrylic acid, methacrylic acid, fumaric acid, maleic anhydride and itaconic acid.

[0010] The number average molecular weight of the polyethylene glycol monoallyl ether is 1500-2400.

[0011] The unsaturated silane monomer is selected from one or a combination of two or more of triisopropylsilyl acrylate, acryloxytrimethylsilane, and acryloxymethyltrimethylsilane.

[0012] Specifically, the organosilicon polycarboxylate water reducer is prepared by a method comprising the following steps:

[0013] In an inert atmosphere, unsaturated carboxylic acid monomers, polyethylene glycol monoallyl ether and unsaturated silane monomers are used as polymerization monomers, an oxidation / reduction system initiator is used as the initiator, and under the action of a chain transfer agent, an aqueous solution free radical polymerization method is used to obtain the product.

[0014] The polymerization temperature is 30-60°C and the polymerization reaction time is 1-3h. The mass fraction of the polymerized monomer in the aqueous solution is 40-60wt%. The amount of the reducing agent in the oxidation / reduction system is 0.5-1wt% of the mass of the carboxylic acid monomer, the polyethylene glycol monoallyl ether, and the silane monomer, and the reducing agent is selected from one or a combination of two or more of ascorbic acid, sodium sulfite, sodium hypophosphite, glucose, and bleaching powder. The amount of the oxidant is 0.5-1wt% of the mass of the carboxylic acid monomer, the polyethylene glycol monoallyl ether, and the silane monomer, and is selected from one or a combination of two or more of hydrogen peroxide, ammonium persulfate, and potassium persulfate. The amount of the chain transfer agent is 0.3-0.5wt% of the mass of the carboxylic acid monomer, the polyethylene glycol monoallyl ether, and the silane monomer, and is selected from one or a combination of two or more of thioglycolic acid, 3-mercaptopropionic acid, and mercaptoethanol.

[0015] Due to the presence of hydrophobic silane monomers, the hydration film layer formed by using silicone polycarboxylate water-reducing agent alone can improve the fluidity of the slurry, but the hydration film layer is too thick and the particles wrapped under the film layer are large and uneven, which will cause water seepage and precipitation, reducing the strength of the consolidated filling material. On the one hand, polymaleic acid has the effect of chelating calcium ions, retarding setting and reducing viscosity. On the other hand, it can also cooperate with silicone polycarboxylate water-reducing agent to form evenly dispersed and uniform solvated particles. Under the synergistic effect of water-retaining agent water-soluble cellulose, it can ensure the good fluidity of the slurry and optimize the mechanical properties.

[0016] The relative molecular mass of the polymaleic acid is 600-1000.

[0017] The water-soluble cellulose has a weight average molecular weight of 100,000 to 500,000 and is selected from one or a combination of two or more of carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose.

[0018] The fly ash is selected from one of Class I fly ash and Class II fly ash, or a combination of the two.

[0019] The present invention also provides a method for preparing the above solid waste-based filling material, comprising the following steps:

[0020] The Bayer red mud, fly ash and desulfurized gypsum are uniformly mixed to obtain a mixture 1, a pumping agent and water are uniformly mixed to obtain a mixture 2, and the mixture 1 and the mixture 2 are uniformly mixed to obtain a solid waste-based filling material.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The filling material of the present invention contains an organosilicon polycarboxylic acid water reducer copolymerized with carboxylic acid monomer, polyethylene glycol monoallyl ether and silane monomer. The chain segments formed by the silane monomer increase the charge density of the hydrophilic region while increasing the hydrophobic region. Through the balance of the hydrophilic and hydrophobic regional structures, the electrostatic repulsion between the solid waste gel particles adsorbed with the water reducer on the surface is enhanced, the solid waste gel particles are prevented from wrapping the water reducer, and the fluidity of the slurry and the strength of the filling material are improved. In addition, under the joint action of the hydrophilic group and the hydrophobic group, a thicker solvated water film will be formed on the surface of the particles such as red mud, which further reduces the viscosity between the particles and improves the fluidity of the slurry. For example, the initial fluidity is above 350 mm, and the 30-minute fluidity retention value is above 320 mm.

[0023] The inventors found that the synergistic effect of organosilicon polycarboxylic acid water-reducing agent, polymaleic acid and water-soluble cellulose can optimize the mechanical properties while ensuring good fluidity of the slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The SEM image and energy spectrum scan of the solid waste-based filling material of Example 1;

[0025] Figure 2 This is the XRD spectrum of the solid waste-based filling material in Example 1. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.

[0027] Polyethylene glycol monoallyl ether 2400 (number average molecular weight 2400) and polyethylene glycol monoallyl ether 1500 (number average molecular weight 1500) were purchased from Hai'an Petrochemical Plant, Jiangsu Province.

[0028] Polymaleic acid with relative molecular weight of 600 and 1000 were purchased from Sinochem.

[0029] The weight-average molecular weight of hydroxyethyl cellulose was 122,000 and it was purchased from Shanghai Zhenzhun Biotechnology Co., Ltd.

[0030] Bayer red mud and Class I fly ash were purchased from Shanxi Senze Energy Technology Group Co., Ltd.; desulfurized gypsum was purchased from Shangqiu Tianyuan Desulfurized Gypsum Co., Ltd. The oxide compositions of the above three raw materials are shown in Table 1:

[0031] Table 1 Raw material oxide composition

[0032] raw material <![CDATA[Al 2 THE 3 ]]> <![CDATA[SiO 2 ]]> <![CDATA[Fe 2 THE 3 ]]> CaO <![CDATA[SO 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> MgO <![CDATA[P 2 THE 5 ]]> Bayer red mud 29.34 23.43 16.013 11.48 1.07 4.39 0.984 11.34 0.74 0.41 Grade Ⅰ fly ash 37.45 47.17 4.00 4.43 1.08 2.65 0.61 0.30 0.39 1.14 Desulfurization gypsum 0.46 2.03 0.41 47.64 48.50 0.04 0.07 0.11 0.56 -

[0033] Example 1

[0034] 1) Under nitrogen atmosphere, 200g acrylic acid, 200g polyethylene glycol monoallyl ether 2400, 80g triisopropyl acrylate, and 1.4g potassium persulfate were added to 720g water, and the temperature was raised to 60°C to mix the monomer solution evenly. After 30min, a solution of 2.8g ascorbic acid, 0.84g mercaptoethanol, and 3.36g water was added dropwise, and the polymerization reaction was carried out for 3h. After the reaction, the pH was adjusted to 7 with sodium hydroxide, and water was removed by distillation under reduced pressure to obtain a silicone polycarboxylic acid water reducer with a weight average molecular weight of 124,000.

[0035] 2) 60 g of Bayer red mud, 40 g of grade I fly ash, and 10 g of desulfurized gypsum are mixed evenly to obtain mixture 1; 5 g of a pumping agent prepared by mixing organosilicon polycarboxylic acid water reducer, polymaleic acid with a relative molecular mass of 1000, and hydroxyethyl cellulose in a mass ratio of 5:5:10 and 35 g of water are mixed evenly to obtain mixture 2; mixture 1 and mixture 2 are mixed evenly to obtain a solid waste-based high-fluidity filling material.

[0036] Example 2

[0037] The rest is the same as Example 1, except that in step 1), an equal mass of polyethylene glycol monoallyl ether 1500 is used instead of polyethylene glycol monoallyl ether 2400, and the weight average molecular weight is 127,000.

[0038] Example 3

[0039] The rest is the same as Example 1, except that in step 1), the amount of triisopropylsiloxy acrylate is 100 g and the weight average molecular weight is 122,000.

[0040] Example 4

[0041] The rest is the same as Example 1, except that in step 1), 150 g of acrylic acid, 400 g of polyethylene glycol monoallyl ether 2400, and 100 g of triisopropylsilyl acrylate have a weight average molecular weight of 122,000.

[0042] Example 5

[0043] The rest is the same as Example 1, except that in step 2), the amount of pumping agent used is 3 g.

[0044] Example 6

[0045] The rest is the same as Example 1, except that in step 2), the pumping agent is compounded by an organosilicon polycarboxylic acid water reducer, polymaleic acid with a relative molecular mass of 1000, and hydroxyethyl cellulose in a mass ratio of 3:5:10.

[0046] Example 7

[0047] The rest is the same as Example 1, except that in step 2), the pumping agent is compounded with an organosilicon polycarboxylic acid water reducer, polymaleic acid with a relative molecular mass of 1000, and hydroxyethyl cellulose in a mass ratio of 5:3:10.

[0048] Example 8

[0049] The rest is the same as Example 1, except that, in step 2), 40g of Bayer red mud, 60g of Class I fly ash, and 10g of desulfurized gypsum are mixed evenly to obtain mixture 1, 3g of a pumping agent composed of a silicone polycarboxylic acid water reducer, polymaleic acid with a relative molecular mass of 600, and hydroxyethyl cellulose in a mass ratio of 5:5:10 and 35g of water are mixed evenly to obtain mixture 2, and mixture 1 and mixture 2 are mixed evenly to obtain a solid waste-based high-fluidity filling material.

[0050] Comparative Example 1

[0051] The rest is the same as Example 1, except that the silicone polycarboxylate water reducer is replaced by an equal mass of BASF polycarboxylate water reducer RHEOPLUS 420.

[0052] The solid waste-based filling materials prepared in the above examples and comparative examples were subjected to the following performance tests:

[0053] 1. Fluidity: Refer to Appendix A.0.2 Fluidity Test in the standard GB / T 50448-2008 Technical Specification for Cement-based Grouting Materials, which requires that the initial expansion be ≥290mm, the 30min fluidity retention value be ≥260mm, and the initial fluidity and 30min fluidity retention value be recorded.

[0054] 2. Water seepage performance: Test with reference to the water seepage test standard in GB / T 50080-2002 Concrete mixture performance test method standard.

[0055] 3. Compressive strength: Tested in accordance with GB / T 50081-2002 Practical Standard for Test Methods of Mechanical Properties of Ordinary Concrete.

[0056] Table 2 Performance test results

[0057]

[0058] Figure 1This is the SEM image of the filling material of Example 1. Through the analysis of the microstructure and elemental composition of the solid waste-based high-fluidity filling material, it can be seen that a type of target product with a characteristic structure of flakes and clusters is generated; the target product is mainly composed of oxides of elements such as Ca, Al, Si, K and Na, and the Al and Si elements overlap significantly, and the Ca and Na elements overlap significantly; this indicates that Example 1 generates an aluminosilicate structure and combines with sodium to form C(N)-SH (sodium-containing calcium silicate hydrate), CASH (calcium aluminosilicate hydrate) and CSH (calcium silicate hydrate).

[0059] It can be seen from Table 2 that the solid waste-based high-fluidity filling material slurry prepared by the present invention has excellent fluidity, and the mechanical properties of the filling material after consolidation are optimized.

[0060] Figure 2 The XRD spectrum of the filling material in Example 1 shows that its main structure is ettringite (Ca 6 Al 2 (SO 4 ) 3 (OH) 12 ·26H 2 O), beryl (Na 8 (Al 8 Si 16 O 48 )·24H 2 O), CASH, calcium alumina (Na 6 Ca 2 Al 6 Si 6 O 24 (CO 3 ) 2 12H 2 O) and CSH. Red mud in solid waste-based filling materials provides a high alkalinity reaction environment, which stimulates the activity of inert silicon and aluminum oxides in the raw materials. The more active silicon and aluminum react with Ca 2+ and OH - reaction, producing more CASH and CSH products. At the same time, the aluminosilicate structure is - depolymerized into AlO 2- , consumes CaSO 4 ·2H 2 O and form more ettringite, thus promoting the development of backfill materials. Among them, ettringite, CASH and CSH are typical hydration products, which make the main contribution to the strength of solid waste-based backfill materials.

[0061] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A solid waste-based high-fluidity filling material, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of Bayer red mud, 40-60 parts of fly ash, 10-20 parts of desulfurized gypsum, 3-5 parts of pumping agent and 30-60 parts of water. The pumping agent is a compound of an organosilicon polycarboxylic acid water reducer, polymaleic acid and water-soluble cellulose in a mass ratio of 3-5:3-5:

10. The organosilicon polycarboxylic acid water reducer is copolymerized by unsaturated carboxylic acid monomer, polyethylene glycol monoallyl ether and unsaturated silane monomer in a mass ratio of 1.5-2:2-4:0.8-1 in the presence of a chain transfer agent.

2. The solid waste-based high-fluidity filling material according to claim 1, characterized in that: The unsaturated carboxylic acid monomer is selected from one or a combination of two or more of acrylic acid, methacrylic acid, fumaric acid, maleic anhydride and itaconic acid.

3. The solid waste-based filling material according to claim 1, characterized in that: The number average molecular weight of the polyethylene glycol monoallyl ether is 1500-2400.

4. The solid waste-based high-fluidity filling material according to claim 1, characterized in that: The unsaturated silane monomer is selected from one or a combination of two or more of triisopropylsilyl acrylate, acryloxytrimethylsilane, and acryloxymethyltrimethylsilane.

5. The solid waste-based high-fluidity filling material according to claim 1, characterized in that: The organosilicon polycarboxylate water reducer is prepared by a method comprising the following steps: In an inert atmosphere, unsaturated carboxylic acid monomers, polyethylene glycol monoallyl ether and unsaturated silane monomers are used as polymerization monomers, an oxidation / reduction system initiator is used as the initiator, and polymerization is performed by aqueous solution free radical polymerization under the action of a chain transfer agent.

6. The solid waste-based high-fluidity filling material according to claim 5, characterized in that: The polymerization temperature is 30-60°C, and the polymerization reaction time is 1-3h; the mass fraction of the polymerized monomer in the aqueous solution is 40-60wt%; the amount of the reducing agent in the oxidation / reduction system is 0.5-1wt% of the total mass of the carboxylic acid monomer, the polyethylene glycol monoallyl ether, and the silane monomer, and the reducing agent is selected from one or a combination of two or more of ascorbic acid, sodium sulfite, sodium hypophosphite, glucose, and bleaching agent; the amount of the oxidizing agent is 0.5-1wt% of the total mass of the carboxylic acid monomer, the polyethylene glycol monoallyl ether, and the silane monomer, and the oxidizing agent is selected from one or a combination of two or more of hydrogen peroxide, ammonium persulfate, and potassium persulfate; the amount of the chain transfer agent is 0.3-0.5wt% of the total mass of the carboxylic acid monomer, the polyethylene glycol monoallyl ether, and the silane monomer, and is selected from one or a combination of two or more of thioglycolic acid, 3-mercaptopropionic acid, and mercaptoethanol.

7. The solid waste-based high-fluidity filling material according to claim 1, characterized in that: The relative molecular mass of the polymaleic acid is 600-1000.

8. The solid waste-based high-fluidity filling material according to claim 1, characterized in that: The water-soluble cellulose has a weight average molecular weight of 100,000 to 500,000 and is selected from one or a combination of two or more of carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose.

9. The solid waste-based filling material according to claim 1, characterized in that: The fly ash is selected from one of Class I fly ash and Class II fly ash, or a combination of the two.

10. The method for preparing the solid waste-based high-fluidity filling material according to any one of claims 1 to 9, characterized in that: The steps include: The Bayer red mud, fly ash and desulfurized gypsum are uniformly mixed to obtain a mixture 1, a pumping agent and water are uniformly mixed to obtain a mixture 2, and the mixture 1 and the mixture 2 are uniformly mixed to obtain a solid waste-based filling material.

Citation Information

Patent Citations

  • Red mud-based fluid swelling filling material

    CN102101788B

  • A Bayer process red mud-based backfill material and its preparation method

    CN111393097B

  • Soil stabilizer as well as preparation method and application thereof

    CN116573900A

  • Multitype-adsorptive-group polycarboxylic acid water-reducing agent, method for preparing the same and use thereof

    US20210198143A1